2004
DOI: 10.4102/ojvr.v71i2.274
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexamethasone and promethazine in combination with buparvaquone in the management of East Coast fever

Abstract: <span>The effects of dexamethasone and promethazine on the amelioration of pulmonary oedema in East Coast fever were investigated. The clinical effects of these drugs were further investigated when used in conjunction with the antitheilerial drug, buparvaquone. In the first experiment, 15 crossbred (Friesian x Zebu) steers were divided into four groups. With the exception of the animals in group IV, that served as a control group all the others were infected with <em>Theileria parva</em> spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Indeed, a study by Silayo et al [16] reported that in absence of acaricide use in cattle kept under extensive grazing system in Tanzania, calf mortalities due to TBDs in particular ECF can reach up to 80%. Calves are infected naturally with haemoparasites within four weeks of birth and in the absence of acaricide application, their health status decline severely and succumb to high mortality rates [17,42]. In addition, in absence of routine use of acaricides, increased morbidities, reduced production and reproduction performance associated with high mortalities in adult cattle has also been reported in different places [18-20,43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study by Silayo et al [16] reported that in absence of acaricide use in cattle kept under extensive grazing system in Tanzania, calf mortalities due to TBDs in particular ECF can reach up to 80%. Calves are infected naturally with haemoparasites within four weeks of birth and in the absence of acaricide application, their health status decline severely and succumb to high mortality rates [17,42]. In addition, in absence of routine use of acaricides, increased morbidities, reduced production and reproduction performance associated with high mortalities in adult cattle has also been reported in different places [18-20,43].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, lung tissues are damaged by inflammatory infiltration, leading to a severe pulmonary edema [10]. These clinical signs of ECF appear during the schizont stage of the parasite and host death can occur before the emergence of piroplasm.…”
mentioning
confidence: 99%
“…The main symptoms of ECF as described by Gwamaka et al . [ 21 ] include fever, swelling of lymph nodes, loss of appetite, excessive salivation and lacrimation, staring hair coat, dry muzzle, dropped ears, ruminal stasis, anorexia, and dyspnea. Anaplasmosis, the disease caused by A. marginale is characterized by progressive hemolytic anemia associated with fever, weight loss, abortion, and decreased milk production [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] include fever, swelling of lymph nodes, loss of appetite, excessive salivation and lacrimation, staring hair coat, dry muzzle, dropped ears, ruminal stasis, anorexia, and dyspnea. Anaplasmosis, the disease caused by A. marginale is characterized by progressive hemolytic anemia associated with fever, weight loss, abortion, and decreased milk production [ 21 ]. Heartwater (caused by E. ruminantium ) is characterized by sudden onset of fever, tachycardia, inappetence, hyperesthesia, high-stepping gait, twitching eyelids, chewing, and hemorrhagic diarrhea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation